2018
DOI: 10.1111/1462-2920.14307
|View full text |Cite
|
Sign up to set email alerts
|

Distributing regionally, distinguishing locally: examining the underlying effects of local land use on airborne bacterial biodiversity

Abstract: Airborne bacteria are abundant and can vary with land use. Urban expansion is increasing rapidly at a global scale, altering natural sources of airborne bacterial biodiversity, as soils and native plants are replaced by pavement and managed yards. Urbanization homogenizes the biodiversity of larger organisms, but its effects are understudied with respect to microbes. This study uses categorical and gradient approaches to examine airborne bacterial communities in southwest Michigan (USA). Airborne communities c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Other vegetation and meteorological variables, while significant, explained far less community variation (Table 1). Consistent with our results, other recent studies also have found airborne bacterial composition to be closely coupled with individual sampling sites (Seifried et al, 2015;Docherty et al, 2018). In contrast, several earlier culture-independent aerobiome studies found spatial location within an urban area to be insignificant compared to the effect of time (e.g., Brodie et al, 2007;Fierer et al, 2008;Bowers et al, 2013).…”
Section: Space Is More Important Than Timesupporting
confidence: 91%
“…Other vegetation and meteorological variables, while significant, explained far less community variation (Table 1). Consistent with our results, other recent studies also have found airborne bacterial composition to be closely coupled with individual sampling sites (Seifried et al, 2015;Docherty et al, 2018). In contrast, several earlier culture-independent aerobiome studies found spatial location within an urban area to be insignificant compared to the effect of time (e.g., Brodie et al, 2007;Fierer et al, 2008;Bowers et al, 2013).…”
Section: Space Is More Important Than Timesupporting
confidence: 91%
“…Dispersal buffered reductions in biomass under drought but also facilitated greater loss of some metabolic functions, and reduced species richness. Drought will continue to grow as a major threat to food production, and microbial dispersal rates can change with land use fragmentation (Bell and Tylianakis, 2016) but are rarely measured (but see Bowers et al, 2011;Docherty et al, 2018). Aerial dispersal could alter the response of soil communities to global change, but predicting the direction of this response will require a greater understanding of the mechanisms at play during changes in dispersal.…”
Section: Discussionmentioning
confidence: 99%
“…This effort has created a growing knowledge base on the microbial community in the atmosphere and has provided a few clues regarding the variability, viability and functionality of this community. However, many questions remain unanswered; although the studies were performed at different locations around the globe (e.g., Europe and the Alps, [8][9][10] Asia, 2,11−13 the Mediterranean, 7,14 North America, 15,16 South America, 17 the Amazon rainforest, 18 and Antarctica 19 ), little is known about the residence time of microorganisms in the atmosphere; the connectivity of microbial communities between regions; the presence of a "core" microbiome in the atmosphere; anthropogenic effects on the atmospheric microbiome; and the role played by the atmosphere in the introduction of new bacteria and functions to different environments, and therefore about the global dissemination of pathogens and antibiotic resistance genes. Finally, the viability and functionality of airborne microorganisms in different niches within the atmosphere, such as clouds vs. dust storms, remain unknown.…”
Section: Introductionmentioning
confidence: 99%